Professoras no cotidiano da educação infantil: um estudo sobre suas concepções do jogo de papéis - Beltrame, Lisaura Maria (2003)
The present research aimed to investigate along child education teachers, how do they conceive the play of the role play, from the teacher’s activity organization and dynamics, in the development and learning of children from 4 to 6 years old. In this way and reflections come out about the importance of the role play in the child education context. In theory, the role play became a theory-practical study in the child education discussions, based on the Vygotsky Historic Cultural Academy, as well as Elkonin, Leontiev, Mukina and others. The research was done in four municipal CEINS in Chapeco (a city in the West Side of Santa Catarina State) in the year of 2002 and 2003. The subsidies of qualitative research were used as the main instrument for collecting data to the semi-structured interview with fifteen teachers. Observations were also done in the classes of child education with cooperated teachers. It was noticed as a research result the majority of child education teacher conceive the play role as the main activity of the children, but they have difficulties and they also don’t prior them in the organizational dynamics of education practice. We believe on this study importance for the possibility to identify and understand the conceptions of the child education teachers, reflecting about their daily education practice, reflecting, though, in a new way of thinking about role play in the children development and learning in children of four to six years old.